Socio-cultural Challenges on Federal Structure Nepal - Yadav, Shiv Kumar (Patan Prospective Journal, 2023)
Socio cultural change is a dynamic concept and change on different time periods. These variables are change and main determinants of political and economic change. The cultural, ethnic and economic diversity across the country is very hard to have homogeneity within such heterogeneous characteristics. Therefore, new minorities are likely to be created within the subunits. Such units and subunits among various socio-cultural and ethnic groups may create instability. The disagreement on the geographical division of the states has already created instability in the Terai region. Why is socially and culturally diverse Asia still overwhelmingly unfederal ? The issue seeks to answer the question by identifying the factors responsible for the adoption of federalism in some countries as well as its rejection in others, with particular reference to existing research and the practices of federalism in India, Pakistan and Malaysia.1 The central argument is that the federal discourse in Asia is to be conjoined to democracy discourse in order to assess the democratic effect of federalism, which is an important key to federal success. On the basis of a conceptual distinction between diversity- claims and equality-claims, it is emphasized that federalism in Asia needs to strike a balance between its concern for management of diversity and for the production of some equity in the social-cultural and economic realms.